Attracting Investment in Bangladesh—Sectoral Analyses : A Diagnostic Trade Integration Study - Kathuria, Sanjay; Mezghenni Malouche, Mariem (Washington, DC: World Bank, 2016)
This is volume 3 of a three-volume publication on Bangladesh’s trade prospects. Bangladesh’s ambition is to build on its very solid growth and poverty reduction achievements, and accelerate growth to become a middle income country by 2021, and share prosperity more widely amongst its citizens. This includes one of its greatest development challenges: to provide gainful employment to the over 2 million people that will join the labor force each year over the next decade. Moreover, only 54.1 million of its 94 million working age people are employed. Bangladesh needs to use its labor endowment even more intensively to increase growth and, in turn, to absorb the incoming labor.